2015
DOI: 10.3389/fchem.2015.00045
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle separation with a miniaturized asymmetrical flow field-flow fractionation cartridge

Abstract: Asymmetrical Flow Field-Flow Fractionation (AF4) is a separation technique applicable to particles over a wide size range. Despite the many advantages of AF4, its adoption in routine particle analysis is somewhat limited by the large footprint of currently available separation cartridges, extended analysis times and significant solvent consumption. To address these issues, we describe the fabrication and characterization of miniaturized AF4 cartridges. Key features of the down-scaled platform include simplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…In our study, the highest dilution was observed for the AF4 fractionated 1xviruses and PEG-viruses, whereas little (~2-fold) or no dilution was observed for the culture supernatants. If needed, dilution can be reduced by using thinner spacers, miniaturized channel design or a slot flow option, where the sample-free buffer zone and the sample-containing zone are separately collected (Müller et al 2015;Prestel et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the highest dilution was observed for the AF4 fractionated 1xviruses and PEG-viruses, whereas little (~2-fold) or no dilution was observed for the culture supernatants. If needed, dilution can be reduced by using thinner spacers, miniaturized channel design or a slot flow option, where the sample-free buffer zone and the sample-containing zone are separately collected (Müller et al 2015;Prestel et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…63,64 For the purpose of nanoparticle separation, asymmetric flow FFF, with one crossflow filtration membrane on the bottom surface, draws greater interest as it has been demonstrated to separate nanoparticles efficiently, such as for the characterization of gold, 65,66 silver, 67,68 and non-metallic nanoparticles. 69,70 Field flow fractionation has a very high throughput and high separation efficiency, and has been proven to separate particles ranging from several nanometers to 100 μm in size. However, extensive optimization is required as each field flow fractionation method needs specific external field magnitudes, sample types, solvents, or membranes for performing efficient separation.…”
Section: Active Separationmentioning
confidence: 99%
“…Adding an ultrafiltration step to the ultracentrifugation protocol enables to increase the purity of the isolated vesicles. [44] Commerciallyavailable ultrafiltration columns have already been widely used to isolate EVs from biofluids [45] or culture cell media. [46] However, the recovery rate may decreasedue to the trapping of EVs in the nano-or micropores of the membrane, which also leads to clogging issues.…”
Section: Size-based Isolationmentioning
confidence: 99%
“…Faster diffusing particles (small ones) are eluted earlier by the faster central streamlines compared to larger ones staying near the accumulating wall. Adapted with permission [44]. Copyright 2014, Elsevier.…”
mentioning
confidence: 99%